Effect of Temperature on the Strength of Snow-Ice - Haynes,F Donald (1978)
Uniaxial compression and tension tests were conducted on polycrystalline snow-ice to determine the effect of temperature on its strength. Test temperatures ranged from -0.1 C to -54 C. Two machine speeds, 0.847 mm/s and 84.7 mm/s were used for the constant displacement rate tests. The compressive strength at -54 C was about one order of magnitude higher than at -0.1 C. The tensile strength at -18 C was about 20% higher than at -0.1 C. The initial tangent and 50% strength moduli are given for the compression tests, while the secant modulus to failure is given for the tension tests. The mode of fracture is discussed and the test results are compared with data from other investigations. Errata sheet inserted.